2023
DOI: 10.2147/ppa.s398666
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Patient-Reported Symptom Item Bank for Patients with Hepatobiliary or Pancreatic Malignancies: A Systematic Review

Abstract: Background Patients with hepatobiliary or pancreatic cancers often experience severe symptoms, resulting in a sharp decline in functioning, poor quality of life, and increased mortality risk. Early and effective management of symptoms allows a better quality of life and reduced mortality, depending on the selection of appropriate assessment of specific symptoms for a defined purpose. We aimed to develop a symptom measurement item bank for hepatobiliary or pancreatic cancers. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(22 reference statements)
0
0
0
Order By: Relevance
“…19 A systematic review aimed to create an item bank of patient-reported symptoms for patients with hepatobiliary or pancreatic malignancies found that 40 self-reported symptoms were present following hepatectomy. 20 A survey on the symptom burden of 160 Chinese patients with PLC who underwent liver resection showed that 100% had fatigue, pain, decreased appetite, dry mouth, and bloating. 21 Of the 19 symptoms evaluated on the MD Anderson Symptom Inventory (MDASI) and the Symptom Module specific to Primary Liver Cancer (TSM-PLC) scales, 11 exhibited a prevalence exceeding 50%, with 5 demonstrating a severity score of ≥ 4.…”
Section: Introductionmentioning
confidence: 99%
“…19 A systematic review aimed to create an item bank of patient-reported symptoms for patients with hepatobiliary or pancreatic malignancies found that 40 self-reported symptoms were present following hepatectomy. 20 A survey on the symptom burden of 160 Chinese patients with PLC who underwent liver resection showed that 100% had fatigue, pain, decreased appetite, dry mouth, and bloating. 21 Of the 19 symptoms evaluated on the MD Anderson Symptom Inventory (MDASI) and the Symptom Module specific to Primary Liver Cancer (TSM-PLC) scales, 11 exhibited a prevalence exceeding 50%, with 5 demonstrating a severity score of ≥ 4.…”
Section: Introductionmentioning
confidence: 99%